Investasi Sktor Pendidikan dan Dampaknya Terhadap Pertumbuhan Ekonomi Indonesia - Poai, Cintia Melisa; Lumolo, Tryas; Kayupa, Olvit Olniwati (Fakultas Ekonomi Universitas KristenTentena, 2025)
This study aims to examine the contribution of investment in the education sector to economic growth in Indonesia. Using a descriptive qualitative approach through literature review, this research analyzes 20 scholarly articles. The findings indicate that educational investment has both direct and indirect impacts in economic growth, particularly through improving the quality of human resources, labor productivity, and the income og small and medium-sized enterprises (SMEs). Education also influences the informal sector, such as agriculture and the creative industries, while reinforcing ethical values in economic practices. On the other hand, the effectivenees of education policies still faces serious challenges, including low budget absorption, unequal access, and weak program evalutation. Therefore , education should be seen not only as a social necessity but also as the long-term economic development strategy. This study recommends data-driven, collaborative, and quality-oriented education policy reforms that prioritize equitable access. Properly managet investment in education has the potential to strengthen the foundation of an inclusive and sustainable national economy.